METODE SPEKTROSKOPI ATR-FTIR TANDEM PCA UNTUK MENDETEKSI KOPI ROBUSTA SEBAGAI ADULTERAN DALAM SEDIAAN KOPI ARABIKA TORAJA KOMERSIAL - Aiyi Asnawi; Erli Berlianti; Ellin Febrina; Nursamsiar Nursamsiar; Sitti Rahmi; Ivan Andriansyah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Toraja arabica coffee is well known for its higher price and quality compared to robusta coffee, but its commercial is often added with other ingredients, including robusta coffee which has low economic value. Visual inspection is unreliable in roasted ground coffee due to the resemblance of its chemical content. The ATR-FTIR method tandem PCA was able to provide an overview of the typical chemical content of the coffee preparation. The purpose of this study was to evaluate the robusta coffee as adulterant in Toraja arabica coffee preparation by using ATR-FTIR. Toraja arabica coffee beans were obtained from three smallholder plantations around Toraja and Robusta coffee beans were obtained from Toraja, Lampung, and West Java coffee plantations. The coffee beans were roasted and then macerated using 96% ethanol for 3Ãƒâ€”24 hours and concentrated using a rotary evaporator until being thick. The IR spectrum of each extract was measured using the ATR-FTIR spectroscopy at a range of 4000-650 cm-1. The results show there is a similarity in the IR spectrum patterns and there is only a small difference in the transmittance of Toraja arabica coffee and robusta coffee. Furthermore, the IR spectrum is clustered by using PCA in R program. The projection of three commercial samples shows that samples 1 and 2 do not contain robusta coffee while sample 3 shows the presence of robusta coffee. In conclusion, the ATR-FTIR spectroscopic method tandem PCA was able to clustered the presence or absence of robusta coffee content in the Toraja arabica coffee.